Pengaruh Likuiditas, Firm Size, dan Profitabilitas Terhadap Nilai Perusahaan (Studi pada Perusahaan Pertambangan yang terdaftar di BEI Periode 2013 - 2017) - Ira Septriana; Haniif Fitri Mahaeswari (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2019)
Firm value is a certain condition that has been achieved by a company as a picture of public trust in the company after through process of activities for several years. Since the company was established until now. The purpose of this study is to find out the impact of liquidity, firm size and profitability on firm value of mining sector companies listed in the IDX over the period 2013-2017. The method of sampling used in this study is the purposive sampling method. The research data are secondary data obtained from Indonesian Capital Market Directory (ICMD) and published financial statements. This analysis technique uses multiple regression analysis techniques. The results of the study show that liquidity and firm size have an influence on the value of the company, while profitability does not have an influence on the value of the company.Keywords : firm value, liquidity, firm size, and profitability